Continuous respiratory monitoring for sleep apnea screening by ambulatory hemodynamic monitor - Dillier, Roger (World journal of cardiology, 2012)
AIM:To validate the sleep-disordered breathing components of a portable electrocardiography and hemodynamic monitor to be used for sleep apnea screening.METHODS:Sleep-disordered breathing(SDB) is associated with cardiovascular disease.Patients with existing cardiovascular disease may have unrecognized SDB or may develop SDB while under the care of a cardiologist.A screening device for SDB,easy to use and appealing to cardiologists,would assist in referral of appropriate patients for full polysomnography(PSG).A cardiac and respiratory monitor(CPAM) was attached to patients undergoing PSG and an apnea/hypopnea index(AHI) generated.The CPAM device produced respiration rate,snoring rate,individual apnea/hypopnea events and an SDB severity score(SDBSS).In addition to AHI,an expert over-reader annotated individual breaths,snores and SDB breathing events to which the automated algorithms were compared.RESULTS:The test set consisted of data from 85 patients(age:50.5 ± 12.4 years).Of these,57 had a positive PSG defined as AHI ≥ 5.0(mean:30.0 ± 29.8,negative group mean:1.5 ± 1.2).The sensitivity and specificity of the SDBSS compared to AHI was 57.9% and 89.3%,respectively.The correlation of snoring rate by CPAM compared to the expert overreader was r = 0.58(mean error:1.52 snores/min),while the automated respiration rate had a correlation of r = 0.90(mean error:0.70 breaths/min).CONCLUSION:This performance assessment shows that CPAM can be a useful portable monitor for screening and follow-up of subjects for SDB.